Achieving precipitation strengthening and retained austenite thinning via strain induced precipitation to improve fatigue wear resistance of bainitic steel - Sida Chen; Zulai Li; Quan Shan (Materials & Design)
Precipitate phases provide precipitation strengthening effects but worsen fatigue properties. A Solid Solution-Forging-Austempering (SFA) process was presented aimed at breaking the trade-off between fatigue performance and hardness of Ti-containing wear-resistant bainitic steel, and the impressive strength-ductility balance of 26.16GPa% was achieved. The SFA process refined the primary TiC and introduced strain-induced TiC with a coherent interface with the matrix. During the cyclic forging process, the grain boundaries pinning effect by strain-induced TiC refined the prior austenite grains which led to a completer bainite transformation during the austempering process, thereby promoting the thinning of retained austenite (RA). The fatigue behavior dominated by RA morphology was delved. Results indicated that the uneven strain distribution inside blocky RA contributed to its uneven transformation to martensite, consequently promoting fatigue crack initiation at interfaces. Conversely, film-like RA exhibited a uniform strain distribution, resulting in a more uniform transformation to martensite. Consequently, film-like RA significantly enhanced the fatigue wear performance of bainitic steel. Since fatigue performance exhibited different dominance over wear performance under different wear conditions, the amount ratio of primary TiC to strain-induced TiC can be altered by adjusting the Ti addition to meet the requirements of fatigue performance under different wear conditions.